Precursor carboxy‐silica for functionalization with interactive ligands. I. Carbodiimide‐assisted preparation of silica‐bonded stationary phases with octadecyl, naphthyl, and anthracenyl ligands: Comparison of their selectivity and retentivity. Issue 24 (8th November 2020) - Paranamana, Nilushi; El Rassi, Ziad
Abstract: A precursor carboxy‐silica support was introduced for grafting retentive ligands for use in high‐performance liquid chromatography. This support was prepared by sequentially reacting 5 μm silica particles with vinyltrimethoxysilane and then thioglycolic acid. The carboxy‐silica thus obtained was subsequently functionalized with octadecylamine, 2‐naphthylamine, or 2‐aminoanthracene by on‐column reactions via a carbodiimide conjugation reaction. The carbodiimide with its zero‐length carboxyl‐to‐amine coupling ability works by activating the surface carboxyl groups of the precursor support for direct reaction with the primary amines of octadecylamine, 2‐naphthylamine, or 2‐aminoanthracene via amide bond formation. These reactions series, which are applied for the first time in high‐performance liquid chromatography column fabrication, yielded the octadecyl‐, naphthyl‐, and anthracenyl‐silica columns. The three columns were evaluated for their reversed‐phase chromatography retention properties with alkylbenzenes, alkylphenyl ketones, nitroalkanes, benzene and toluene derivatives, polyaromatic hydrocarbons, and nitro‐substituted amino acids. The naphthyl‐ and anthracenyl‐silica exhibited a good selectivity and efficiency toward most of the aromatic analytes when compared to the octadecyl‐silica. Nitro‐substituted amino acids containing electron withdrawing groups showed greater selectivity than other analytes on the aromatic‐based columns than the C18 column. This is because of the ability of the π electron system of the analyte to accept electrons from the aromatic‐based stationary phase (a Lewis base).